Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kepuasan kerja Guru - Cindy Maharati (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2021)
Teachers are the spearhead and mover of educational progress, not limited to routines carrying out obligations with rewards set by the government. Because it is not easy to bear the burden as a teacher. Teachers are faced with internal problems that are still complex, accompanied by demands to promote cultured education. The purpose of this study was to analyze the simultaneous, partial and dominant influence of work motivation and work environment on teacher job satisfaction. This type of research is explanatory research to analyze the influence between two variables of Work Motivation and Work Environment on Teacher Job Satisfaction. The research population was the teacher of Riyadlul Jannah Pacet Junior High School, Mojokerto. The number of samples is 49 people, while the data analysis uses multiple linear regression. The results showed that: 1) There was a simultaneous influence of work motivation and work environment on job satisfaction. 2) There is a partial effect of work motivation on job satisfaction and there is a partial effect of work environment on job satisfaction. 3) the work environment has a more dominant effect on job satisfaction than work motivation.